Odorant receptors of a primitive hymenopteran pest, the wheat stem sawfly. Issue 6 (22nd August 2013) - Gress, J. C.; Robertson, H. M.; Weaver, D. K.; Dlakić, M.; Wanner, K. W.
Abstract: The wheat stem sawfly, Cephus cinctus, is an herbivorous hymenopteran that feeds exclusively on members of the Graminae family. Synanthropically, it has become one of the most important insect pests of wheat grown in the northern Great Plains region of the USA and Canada. Insecticides are generally ineffective because of the wheat stem sawfly's extended adult flight period and its inaccessible larval stage, during which it feeds within the wheat stems, making it virtually intractable to most pest management strategies. While research towards integrated pest management strategies based on insect olfaction has proved promising, nothing is known about the molecular basis of olfaction in this important pest species. In this study we identified 28 unique odorant receptor (Or) transcripts from an antennal transcriptome. A phylogenetic analysis with the predicted Ors from the honey bee and jewel wasp genomes revealed at least four clades conserved amongst all three Hymenoptera species. Antennal expression levels were analysed using quantitative real‐time PCR, and one male‐biased and five female‐biased Ors were identified. This study provides the basis for future functional analyses to identify behaviourally active odours that can be used to help develop olfactory‐mediated pest management tools.